Multimedia Communications, Services and Security 8th International Conference, MCSS 2015, Kraków, Poland, November 24, 2015. Proceedings - Dziech, Andrzej; Leszczuk, Mikołaj; Baran, Remigiusz (Communications in Computer and Information Science, 2015)
This volume constitutes the refereed proceedings of the 8th International Conference on Multimedia Communications, Services and Security, MCSS 2015, held in Krakow, Poland, in November 2015. The 16 full papers included in the volume were selected from 39 submissions. The papers cover ongoing research activities in the following topics: multimedia services; intelligent monitoring; audio-visual systems; biometric applications; experiments and deployments.